Introduction (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
The articles in this special issue cover a range of topics related to coloniality, language ideologies, language policy and classroom practice in Malawi, Namibia, Zambia and Zimbabwe. The findings and conclusions reached have relevance not just to southern African countries, but to the so-called Global South generally.